Metabolome-Microbiome Responses of Growing Pigs Induced by Time-Restricted Feeding - Wang, Hongyu; Xia, Pengke; Lu, Zhiyang; Su, Yong; Zhu, Weiyun (Frontiers in Veterinary Science, 2021)
Time-restricted feeding (TRF) mode is a potential strategy for improving health and production. However, the effects of TRF on the gut microbiota and metabolism of the host in the large intestine remains unclear. Therefore, the present study aimed to investigate the microbiome and metabolome changes induced by TRF based on a growing pig model. Twelve crossbred growing barrows were randomly allotted into 2 groups, namely free-access feeding group (FA) and TRF group. Pigs in the FA group were fed free access while the TRF group were fed free access within regular time at 07:00-08:00, 12:00-13:00, 18:00-19:00, respectively. Results showed that TRF increased the concentrations of NH4-N, putrescine, cadaverine, spermidine, spermine, total biogenic amines, isobutyrate, butyrate, isovalerate, total SCFA and lactate while decreased the pH value in colonic digesta and the concentration of acetate. TRF had no significant effects on the Fisher index, Simpson index, ACE index, Chao1 index, and Observed species of the colonic bacterial community but increasing the Shannon index. The relative abundances of Prevotella 1, Eubacterium ruminantium group were significantly increased in the TRF group while the relative abundances of Clostridium sensu sticto 1, Lactobacillus, Eubacterium coprostanoligenes group were decreased compared with the FA group. PLS-DA analysis revealed an obvious and regular variation between FA and TRF groups, further pathway enrichment analysis showed that these differential features were mainly enriched in pyrimidine metabolism, nicotinate and nicotinamide metabolism, glycerolipid metabolism, fructose and mannose metabolism. In addition, Pearson’s correlation analysis indicated that the changes in microbial genera were correlated with the colonic metabolites. In conclusion, these results together indicated that although the overall microbial composition in the colon was not changed, TRF induced the gradient of the nutrients and metabolites which were correlated with certain microbial genera including Lactobacillus, Eubacterium_ruminantium group, Eubacterium coprostanoligenes group, Prevotella 1, and Clostridium sensu sticto 1. However, more studies are needed to understand the impacts of TRF on the health and metabolism of growing pigs.